Lingwistyczne aspekty komunikacji językowej osób starszych - Stolarczyk-Zielonka, Monika (Investigationes Linguisticae, 2010)
The main purpose of the herein article is to describe the language and curiosity of the elderly people communication. This article presents basic biological, social and psychological changes occurring together with ageing and their impact on the elderly people linguistic attributions. All enclosed conclusions are supported by professional literature as well as by remarks coming from the field research carried out among people over 60 years old.